Kadar Kolesterol pada Mencit (Mus-Musculus) Diabetes Setelah Konsumsi Ekstrak Rumput Laut Coklat (Phaeophyta) - Irene Fransiska; Didin Erma Indahyani; Ari Tri Wanodyo Handayani (Pustaka Kesehatan, 2020)
In the case of Diabetes Mellitus, it will trigger some changes in lipid metabolism and lipoprotein composition, one of them is cholesterol. Cholesterol is a lipid that plays an important role in the structure of cell membranes. Seaweed contains bioactive components of flavonoids which reduce cholesterol levels. Brown seaweed contains bioactive components of alkaloids, flavonoids, triterpenoids, saponins, phenol hydroquinone, tannins, chlorophyll and β-carotene pigments. The bioactive component of brown seaweed also has strong antioxidant activity that can prevent damage caused by oxidative stress on pancreatic β cell function and acts as a trap for various free radicals and can reduce diabetic rat lipid peroxidation. This study to analyze the effect of giving brown seaweed extract on cholesterol levels in diabetic mice.This study was divided into 4 sample groups, namely the normal group, negative controls (diabetic mice), positive controls (diabetic mice + 1.3 mg / 20 gr BB metformin), K1 (diabetic mice + brown seaweed extract). The seaweed dose of 10mg / 20grBB is given on a daily basis for 21 days. Checking blood cholesterol levels in serum using the POD CHOD method and measured using biolysers. Diabetic mice with brown seaweed extract were significantly (p <0.05) lower cholesterol level of 68.94 mg / dL than diabetic mice 81.75 mg / dL. It was concluded that brown seaweed extract had an effect on reducing total cholesterol levels in diabetic mice. Keywords : Cholesterol levels, Diabetic mice, Brown Seaweed